2022
DOI: 10.3892/mmr.2022.12747
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MNX1‑AS1 promotes prostate cancer progression through regulating miR‑2113/MDM2 axis

Abstract: A growing number of dysregulated long non-coding (lnc)RNAs have been verified to serve an essential role in human prostate cancer. However, the underlying mechanisms of lncRNA MNX1 Antisense RNA 1 (MNX1-AS1) in prostate cancer has not been explored. Therefore, the present study aimed to explore the function of MNX1-AS1 in prostate cancer tumorigenesis and investigate the in-depth mechanism. The expression of MNX1-AS1, microRNA (miR)-2113 and murine double min 2 (MDM2) in prostate cancer tissues and correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Until now, the miRNAs implicated in sepsis-induced ALI are largely unknown. miR-2113 has been reported to mediate cell proliferation and apoptosis [ 10 , 25 ]. In this research, we supplied compelling evidence supporting the function of miR-2113 in sepsis-induced ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the miRNAs implicated in sepsis-induced ALI are largely unknown. miR-2113 has been reported to mediate cell proliferation and apoptosis [ 10 , 25 ]. In this research, we supplied compelling evidence supporting the function of miR-2113 in sepsis-induced ALI.…”
Section: Discussionmentioning
confidence: 99%
“…The sodium pentobarbital was mixed with sterile saline to make a 3% solution and injected intraperitoneally at a dose of 50 mg/kg (1-1.25 mg per mouse). 25 The mice were sacrificed by cervical dislocation and mortality was confirmed by cessation of heartbeat. The excised tumors were weighed at 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have found that prostate cancer is closely related to the expression of lncRNAs. For example, the expression of MAGI2-AS3 and MEG3 in lncRNAs inhibits the development of prostate cancer [60,61], and MNX1-AS1 indirectly promotes the development of prostate cancer through expression [62]. We used it as the second disease in the case study, and the experimental outcomes are presented in Table 9.…”
Section: Case Studymentioning
confidence: 99%